2, 5‐hexanedione induced apoptosis of rat bone marrow mesenchymal stem cells by reactive oxygen species. Issue 2 (25th May 2016) - Liu, Shuang; Chen, Feng; Wang, Longjuan; Sun, Wenchang; Liu, Qigui; Chen, Haibo; Su, Dan; Jiang, Yue; Piao, Fengyuan; Sun, Xiance; Sun, Wenfang
Abstract : Objectives: n‐Hexane, a common industrial organic solvent, causes multiple organ damage, especially neurotoxicity, which is proved to be caused by its metabolite 2, 5‐hexanedione (2, 5‐HD). We previously showed that 2, 5‐HD induced apoptosis of rat bone marrow mesenchymal stem cells (BMSCs) . In the current study, we explored the mechanism of 2, 5‐HDinduced apoptosis, especially the role played by reactive oxygen species (ROS) . Methods: Intracellular ROS levels after 2, 5‐HD treatment were measured by the dichloro‐dihydro‐fluorescein diacetate (DCFH‐DA) method, and the antioxidant N‐acetyl cysteine (NAC) was used to scavenge ROS. Apoptosis, mitochondrial membrane potential (MMP), and caspase‐3 activity were measured after 2, 5‐HD exposure with or without NAC pretreatment. Results: In rat BMSCs, 20 mM 2, 5‐HD significantly increased ROS levels and apoptosis. In addition, MMP activity was decreased and caspase‐3 activity was increased. With NAC pretreatment, ROS increases were prevented, cells were rescued from apoptosis, and both MMP and caspase‐3 activity returned to normal levels. Western blotting analysis of malondialdehyde‐modified proteins and superoxide dismutase (SOD) 1 showed that after 2, 5‐HD exposure, BMSCs had oxidative damage and abnormal SOD1 expression. These returned to normal when cells were pretreated with NAC in addition to 20 mM 2, 5‐HD. Furthermore, the expressions of NF‐κB p 65 / RelA and phospho‐NF‐κB p 65 / RelA (Ser 536) were suppressed after 2, 5‐HD exposure and restored by NAC pretreatment. Conclusions: 2, 5‐HD‐induced apoptosis in rat BMSCs is potentially mediated by excessive ROS production.